Review of Zoning System and Passenger and Vehicle Flow Patterns at ASDP Ferry Port, Bitung Branch - Muhamad Fahmi Amrillah; Pierre Marcello Lopulalan; Yulia Puspita Sari; Muhammad Ilham Dwi Saputra (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
ASDP Ferry Port Bitung Branch is one of the ports located in North Sulawesi Province, precisely in Bitung City. This port has an important role in Bitung City, namely as an access for crossings between islands and provinces in the Sulawesi region. Currently, ASDP Ferry Port Birung Branch has not implemented a zone system in accordance with applicable regulations which has resulted in sterilization at the port and irregularities in the flow of passenger and vehicle traffic at the port. This is because the facilities in Zone A1, namely the ticket machine at the port gate, are still not functioning so that unauthorized vehicles can enter the port at will, the weighbridge is not functioning so that ships with excess loads can still board the ship and the toll gate is not functioning as a place to sell vehicle tickets so that drivers must get off first to buy tickets in the waiting room and there is no special lane for passengers who will get on or off the ship. The analysis of the problem then used an analysis guided by the Regulation of the Minister of Transportation Number 91 of 2021 concerning Zoning in Port Areas Used to Serve Ferry Transportation and the Decree of the Director General of Land Transportation Number SK,242/HK.104/DRJD/2010 concerning Technical Guidelines for Crossing Traffic Management as a guideline for the analysis of the addition of supporting equipment for the zoning system and flow patterns referring to the Regulation of the Minister Number 13 of 2014 concerning Traffic Signs. Based on the results of the analysis above, in order to create a safe and orderly crossing port, the ASDP Ferry Port, Bitung Branch can determine the zoning system and regulate the flow patterns of passengers and vehicles at the ASDP Ferry Port, Bitung Branch, in this case it is also necessary to add facilities and restore the function of several facilities such as Tollgates and weighbridges